If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 12 = 40 Reorder the terms: 12 + X = 40 Solving 12 + X = 40 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + X = 40 + -12 Combine like terms: 12 + -12 = 0 0 + X = 40 + -12 X = 40 + -12 Combine like terms: 40 + -12 = 28 X = 28 Simplifying X = 28
| (b)(b)(a-3)-(a-3)= | | 9+p=14 | | 25=13+3s | | y=9x^2-27x+20 | | a(z)(z)-9+b(z)(z)-9= | | 9n-3=10n-9 | | 8t-3=5t | | 2x+7-x=15 | | -3-4y=-3y | | m*2=42 | | 2(x+2.3)=x+6.5 | | sq(2x-3)-1=0 | | 11x+4y=18 | | 4n+5(2n-1)=65 | | 0.3x+7.5=11.1 | | 0.7t=0.6+0.9t | | 43w=7w-15w-5w | | 6n+2=4n+12 | | c-9=24 | | 6(x-7)+2x=0 | | 8c-10=3(6-2s) | | -9s-5=9-6s+10 | | -4t+6=2 | | Y=.50(0)+6 | | 4x^3-15x^2=0 | | (b)(b)-15b=-50 | | 3z-1=-7 | | 2c+1=-5 | | y^2-16y+16=14 | | 9x-(4x+9)=3x-35 | | 60=6(2x-4) | | 3x^2+bx+1=0 |